Keunikan Metode Tafsir Al-Quranil Azhim Al-Adzim Karya Ibnu Katsir - Nabilah Nuraini; Dinni Nazhifah; Eni Zulaiha (Bayani, 2022)
Ibn Kasir belongs to the Middle Ages Mufassir (8th century AH / 15th century AD), but in terms of methods and forms of interpretation, Ibn Kasir is in the "middle" position. In other words, he is officially in a classical position because he uses the form of interpretation of Bil Matsur. Ibn Kathir's method uses the tahlili method. In addition, in the interpretation of Ibn Kathir there is a special method that can be found with the analysis carried out by the author on the Tafsir of Ibn Kathir. In this study, the researchers used a type of literature study that has a descriptive qualitative method. From the literature review, it can be seen that the data collection techniques in this study were taken from various written data sources by combining the data generated and analyzed inductively.